2017
DOI: 10.2174/1874306401711010041
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nasal Non-Invasive Ventilation with a RAM Cannula in the Outpatient Home Setting

Abstract: Background:Nasal non-invasive-ventilation (Nasal NIV) is a mode of ventilatory support providing positive pressure to patients via a nasal interface. The RAM Cannula is an oxygen delivery device that can be used as an alternative approach to deliver positive pressure. Together they have been successfully used to provide respiratory support in neonatal in-patient settings.Objective:To describe the outpatient use of Nasal NIV/RAM Cannula as a feasible alternative for home respiratory support in children with chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…There are many factors that affect the mean airway pressure delivered to an infant on nasal CPAP. These include the seal of the nasal interface, loss of pressure through the mouth, the resistance of the airways, as well as the resistance of the device 1 13 14. This study assessed the pressure differential created by the intrinsic resistance of commonly used nasal CPAP interfaces; this is of potential clinical importance as lower resistance interfaces will result in less pressure loss during delivery of gas to the infant’s upper airway.…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors that affect the mean airway pressure delivered to an infant on nasal CPAP. These include the seal of the nasal interface, loss of pressure through the mouth, the resistance of the airways, as well as the resistance of the device 1 13 14. This study assessed the pressure differential created by the intrinsic resistance of commonly used nasal CPAP interfaces; this is of potential clinical importance as lower resistance interfaces will result in less pressure loss during delivery of gas to the infant’s upper airway.…”
Section: Discussionmentioning
confidence: 99%
“…It may be difficult to find a well-fitted interface for children with facial deformity [141,154]. Case series studies reported a successful use of a humidified high-flow nasal cannula (HFNC) with a regular CPAP device [158] or of the nasal RAM cannula [159] with a NIV device for children who did not tolerate a commercial interface. Recently, a nasal cloth mask has become available for children > 2 years of age who have plastic intolerance [160].…”
Section: And 42)mentioning
confidence: 99%
“…4,8,15,16 The Ramanathan (RAM) nasal cannula is an interface used to deliver either CPAP or BiPAP. 2,[17][18][19][20] Use of the RAM cannula originated in the neonatal intensive care unit where it is associated with reduced extubation failure and intubation rates in children with neonatal respiratory distress syndrome. 18,19 This interface has since been applied in the PICU in infants and young children with bronchiolitis or pneumonia with the anecdotal premise that it is better tolerated than mask interfaces.…”
Section: Introductionmentioning
confidence: 99%